2015
DOI: 10.1007/s11926-015-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism and Bone Health

Abstract: Bone pain, proximal muscle weakness, skeletal deformities, and pathological fractures are features of osteitis fibrosa cystica which occur in severe primary hyperparathyroidism (PHPT). In this condition, bone mineral density is usually extremely low, but may be reversible after parathyroidectomy. On X-ray, bone abnormalities are described as having a salt-and-pepper appearance in the skull, with bone erosions and resorption of the phalanges, brown tumors and cysts, as well as diffuse demineralization, along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 55 publications
1
19
0
1
Order By: Relevance
“…Several studies have reported significant BMD gain following parathyroidectomy [14][15][16][17]26,28]. The BMD was lower in patients with severe PHPT and significant improvements were observed after surgical cure, which is consistent with our results [17,29]. Skeletal abnormalities regressed and osteoclastoma shrunk with BMD gain following successful parathyroidectomy in severe PHPT [9,30,31].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported significant BMD gain following parathyroidectomy [14][15][16][17]26,28]. The BMD was lower in patients with severe PHPT and significant improvements were observed after surgical cure, which is consistent with our results [17,29]. Skeletal abnormalities regressed and osteoclastoma shrunk with BMD gain following successful parathyroidectomy in severe PHPT [9,30,31].…”
Section: Discussionsupporting
confidence: 90%
“…Other causes of hyperparathyroidism due to a normal physiological stimulus to increased PTH levels — secondary hyperparathyroidism states — should be excluded (BOX 2). Bone resorption inhibitors, such as bisphosphonates and denosumab, usually cause increases in serum PTH concentrations, rendering a diagnosis of normocalcaemic PHPT under these conditions uncertain 120,121 . The diagnosis of parathyroid gland autonomy in the setting of chronic kidney disease is more challenging.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…However, skeletal involvement continues to be readily detected by technologies such as DXA 15 , 21 . Reduced BMD is observed most often in distal 1/3 radius site, comprised mostly of cortical bone, with relative preservation of lumbar spine, a site that is endowed primarily with trabecular bone 22 . However, these densitometric findings are not consistent with epidemiological data that have consistently reported a greater incidence of fractures at trabecular (vertebral) as well as cortical (non-vertebral) sites in PHPT.…”
Section: Clinical Presentationmentioning
confidence: 99%